2023
DOI: 10.1002/mds.29356
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Water Imaging of the Substantia Nigra in GBA Pathogenic Variant Carriers

Abstract: Background Pathogenic variants in the glucocerebrosidase gene (GBA) have been identified as the most common genetic risk factor for Parkinson's disease (PD). However, the features of substantia nigra damage in GBA pathogenic variant carriers remain unclear. Objective We aimed to evaluate the microstructural changes in the substantia nigra in non‐manifesting GBA pathogenic variant carriers (GBA‐NMC) and PD patients with GBA pathogenic variant (GBA‐PD) with free‐water imaging. Methods First, we compared free wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, recent studies with the PPMI dataset observed that GBA-PD patients had lower striatal and standard uptake value ratios (SUVr) of extra-striatal dopamine transporter (DAT), and had higher free water values in the posterior substantia nigra at baseline than in early-iPD and late-iPD groups. 19,35 Previously, we reported the impact of GBA variants on motor and cognitive impairment in PD patients. GBA-PD had faster motor and cognitive progression than iPD, particularly in bradykinesia, axial impairment, and visuospatial/executive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies with the PPMI dataset observed that GBA-PD patients had lower striatal and standard uptake value ratios (SUVr) of extra-striatal dopamine transporter (DAT), and had higher free water values in the posterior substantia nigra at baseline than in early-iPD and late-iPD groups. 19,35 Previously, we reported the impact of GBA variants on motor and cognitive impairment in PD patients. GBA-PD had faster motor and cognitive progression than iPD, particularly in bradykinesia, axial impairment, and visuospatial/executive function.…”
Section: Discussionmentioning
confidence: 99%
“…GBA ‐PD patients may simultaneously satisfy the conditions of this positive feedback loop, forming a self‐propagating mechanism. Furthermore, recent studies with the PPMI dataset observed that GBA ‐PD patients had lower striatal and standard uptake value ratios (SUVr) of extra‐striatal dopamine transporter (DAT), and had higher free water values in the posterior substantia nigra at baseline than in early‐iPD and late‐iPD groups 19,35 …”
Section: Discussionmentioning
confidence: 99%